Attention allocation in sprinters in prestart state - Ermolaev, B. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to identify contradictions between two forms of sensitivity: to the situation (readiness for a starting shot) and to own movement patterns (biomechanics of own body, own move-ments), as well as to search for possible "marks" of conflict in the implementation of executive actions when distributing attention in a prestart state. Methods and structure of the study. We analyzed the results of the semifinal race at a distance of 60 m for men at the World Athletics Indoor Championships (Birmingham, 2018, Portland, 2016, Sopot, 2014) - 9 runs, 69 results. The sprinter`s startle response time (latent period of the motor reaction) and demon-strated result served as initial indicators. It was assumed that the startle response time was an integral in-dicator of the sprinter`s sensitivity to the starting time. Another integral indicator of the focus and concentration of the athlete`s attention on himself and his movement patterns, achievement of the "perceptual-motor pool" is the time of running the distance - the difference between the demonstrated result and the startle response time. Results and conclusions. We detected a moderate negative correlation between two forms of sensitivity in the athletes: to the starting situation (starter signal) and to own biomechanics. The dependence was in-terpreted as the result of attention allocation in the prestart state. There are concepts according to which attention is viewed as an attribute of control processes aimed to overcome a trend to mechanically per-form well-learned actions. In terms of such an action, it seems to be impossible to pre-configure all the characteristics of attention (control mechanism) to previously unknown parameters of coordinated motor tasks, to form their overall stable "coordination structure".